Confessions of a spoilsport : my life and hard times fighting sports corruption at an old eastern university - Dowling, William C. (Pennsylvania State University Press, 2007)
The author recounts his failed efforts, along with other professors, students and alumni, to get Rutgers University out of the National Collegiate Athletic Association Division I-A during the mid-1990s, maintaining the colleges today sacrifice academics in order to build nationally competitive athletic programs.